Interfaces da comunicação e saúde na mídia impressa - Emerich, Tatiana Breder (2015)
The field of Health Communication encompasses both the peculiar knowledge to communication as the knowledge of the health area, which treated together and explored the potential of each science, interrelate, interact and converge to a broad interdisciplinary field. The objective of this study was to understand and discuss, based on the opinions of individuals, the dynamics of media dissemination of health / disease in print of the Espírito Santo (ES) and identify possible neglected health issues. This is a qualitative study involving interviews with key actors involved in the discussion / placement of health / disease in the two main state newspapers: A Tribuna and A Gazeta, managers of the Health Secretary (SESA ) as well as members of the SESA Communication Department and health counselors representative of users at the State Board of Health. The empirical data collected was analyzed by Content Analysis from the subject. The understanding of the relationships that permeate the print media and the health media disclosure in the ES resulted in important notes which may assist journalists and communicators in the transmission of information related to Public Health clearly, ethics and politics and which meets the needs of health. The interfaces of the relations between the actors interviewed and understanding the dynamics of health news, were identified Diseases neglected by the media and identified strategies to deal with this silencing media. It is concluded that among the Communication and Health Field interfaces is the relationship with the field of public health and therefore the suggestions to face the media neglect of some themes include a training in Public Health for newspaper reporters; the mobilization of patients; management encourage public agenda; and social participation.